Morfologie, chemická struktura, vlastnosti a možnost využití pšeničného B- škrobu - Šárka, Evžen; Bubník, Zdeněk (Chemické listy, 2010)
Compared to other cereal or tuber starches, wheat starch shows mainly two different types of granules, the A-starch and B-starch, which are separated in starch processing. These types differ not only in size or shape but also in chemical structure of amylopectin, arrangement in granules, and lipid and protein contents. Chemical composition and structure of starch influence on physicochemical properties (specific surface, crystallinity, gelatinization characteristics) and functionality. Processing of B-starch (filtration, drying) is problematic for its small particles. Nevertheless, the challenge for other uses of B-starch has been taken up in designing new technological processes. Hence B-starch becomes a valuable raw material in other processes. Examples of its applications in enzymatic processes producing syrups, in modifications affording tailor-made starches, for flavour carriers, baking, extrusion and, last but not least, in biodegradable polymers are given.
Keywords: Food Technology; amylopektin; financování organizované; vztahy mezi strukturou a aktivitou; Financing, Organized; Structure-Activity Relationship; potravinářská technologie; amylosa; Amylopectin; Amylose; škrob; Starch